2012
DOI: 10.1521/soco.2012.30.6.715
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Biological Understanding of Mortality Salience (And Other Threat Compensation Processes)

Abstract: Terror management theorists have proposed explanations of why death anxiety has a special status beyond other anxieties and furthermore argue that awareness of death elicits a defense mechanism that is qualitatively different from other sorts of threat-defense mechanisms. Our review suggests that the biological mechanisms through which thoughts of mortality motivate defensive behavior are not unique. rather, we propose that an evolutionarily primitive, biologically based anxiety system underlies mortality sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 90 publications
(91 reference statements)
1
62
0
Order By: Relevance
“…The biological underpinnings of mortality salience may be not mapped on a specific neural system but rather on a set of areas representing the neural reactivity to uncertainty [59]. It should be emphasized that death was not rated as the worst option in several of the measured circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The biological underpinnings of mortality salience may be not mapped on a specific neural system but rather on a set of areas representing the neural reactivity to uncertainty [59]. It should be emphasized that death was not rated as the worst option in several of the measured circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we have presented evidence from three studies that shed light on several previously uninvestigated questions that have recently gathered much attention in the existential threat literature (Tritt et al, 2012; Jonas et al, 2014). We found that (a) MS causes BIS activity, as indexed by right-hemispheric asymmetric activation in the frontal cortex (measured by the LBT in Study 1 and EEG in Study 2), (b) BIS activity mediates MS effects on cultural closed-mindedness (operationalized as reluctance to explore foreign cultures in Study 1 and ethnocentrism in Studies 2 and 3), and (c) these effects are particularly strong for persons inclined to experience discomfort when faced with unfamiliar and potentially threatening stimuli (measured by NFC in all studies).…”
Section: Discussionmentioning
confidence: 94%
“…Future studies may be able to capture parallel antagonistic processes of inhibition and excitation coupled with the different meaning of the images that could account for effects associated with more general threat processing and more specific death-related processing. Accounting for both general and specific aspects of threat and death cognition will foster the integration of biological theories of existential threat (Tritt et al, 2012) with the most recent version of TMT (Pyszczynski et al, 2015). Low and high energy stimuli were paired to both D and T stimuli in separate blocks and the order of the pairing was counterbalanced across participants.…”
Section: Discussionmentioning
confidence: 99%
“…Highly relevant to the present study are alternative models that emphasise the biological implausibility of a unique and specific threat mechanism of action of death cognition compared to other threats (McGregor, 2006;Tritt et al, 2012). The few studies that investigated possible brain correlates of death reminders have thus far endorsed the TMT predictions.…”
Section: "I'm Not Afraid Of Death; I Just Don't Want To Be There Whenmentioning
confidence: 96%